Influence of Calcium Phosphate and Apatite Containing Products on Enamel Erosion - A. Kensche; S. Pötschke; C. Hannig; G. Richter; W. Hoth-Hannig; M. Hannig (The Scientific World Journal)
For the purpose of erosion prevention the present study aimed to compare the efficacy of two biomimetic products and a fluoride solution to optimize the protective properties of the pellicle. After 1 min of in situ pellicle formation on bovine enamel slabs, 8 subjects adopted CPP-ACP (GC Tooth Mousse), a mouthwash with hydroxyapatite microclusters (Biorepair), or a fluoride based mouthwash (elmex Kariesschutz) for 1 min each. Afterwards, samples were exposed in the oral cavity for 28 min. Native enamel slabs and slabs exposed to the oral cavity for 30 min without any rinse served as controls. After oral exposure, slabs were incubated in HCl (pH values 2, 2.3, and 3) for 120 s and kinetics of calcium and phosphate release were measured photometrically; representative samples were evaluated by SEM and TEM. The physiological pellicle reduced demineralization at all pH values; the protective effect was enhanced by fluoride. The biomimetic materials also reduced ion release but their effect was less pronounced. SEM indicated no layer formation after use of the different products. However, TEM confirmed the potential accumulation of mineral components at the pellicle surface. The tested products improve the protective properties of the in situ pellicle but not as effectively as fluorides.